Pediatric ENT - Graham, John M. (Springer Berlin Heidelberg, 2007)
In recent years there has been increasing sub-specialization and a rapid expansion of the range of therapies available to pediatric ENT specialists. This concise, up-to-date textbook deals comprehensively with all the practical and theoretical aspects necessary for those taking exams or wishing to up-date their knowledge. It is divided into sections covering rhinology, otology and head and neck problems. The uniformly structured chapters cover all relevant topics comprehensively and succinctly. The authors are from Europe and the US and are internationally renowned experts in their fields. This useful and reader-friendly textbook will not only be inspirational to young specialists with an interest in pediatric ENT, but also to those who are due to take their final exams as well as for established specialists in the field. A paediatric overview of children seen in the ENT outpatient department -- Nursing aspects of paediatric ENT -- Anaesthesia for paediatric ENT surgery -- The evolution of speech and language -- Evidence-based management of speech and language delays -- Paediatric voice -- Genetics of non-syndromic deafness -- ENT-related syndromes -- EXIT – antenatal (pre-natal) diagnoses and management -- The immunocompromised child -- Cystic fibrosis and primary ciliary dyskinesia -- Head and neck masses -- Paediatric ENT in developing countries -- Tonsils and adenoids -- The causes and effects of obstructive sleep apnoea in children -- Cleft lip and palate -- Salivary gland disease in childhood -- drooling salivary incontinence (sialorrhoea) -- Congenital cysts, sinuses and fistulae -- Airway endoscopy and assessment in children -- Emergency management of the paediatric airway -- Congenital disorders of the larynx, trachea and bronchi -- Acquired disorders of the larynx in children -- Laryngeal webs and subglottic hemangiomas -- Post-intubation laryngotracheal stenosis -- Congenital and acquired tracheal stenosis in children -- Tracheomalacia in children -- Tracheostomy: an ancient life saver due for retirement, or vital aid in modern airway surgery? -- Recurrent respiratory papillomatosis -- Pharynx and oesophagus -- Paediatric thyroid disease -- Nasal foreign bodies, epistaxis and nasal trauma -- Management of choanal atresia -- Allergic rhinitis -- Rhinosinusitis in children -- Management of the deaf child -- Audiometric testing of children -- Otoplasty and common auricular deformities -- Diagnosis and management strategies in congenital middle and external ear anomalies -- Imaging of the deaf child -- Acute otitis media in children -- Otitis media with effusion -- Chronic otitis media -- Bone-anchored hearing aid (BAHA) and softband -- Cochlear implantation in children -- The dizzy child -- The facial nerve.